ANALYSIS OF FACTORS INFLUENCING DECISION PURCHASE OF STUDENTS FASHION PRODUCTS - Muh Fahrurrozi; Dukha Yunitasari; Mispandi Mispandi (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
Students are an important market segment in the fashion industry, regarding Consumer Preferences, and are often influenced by peers and social media in making purchasing decisions. This study aims to determine the factors that influence the purchasing decisions of fashion products in students of the Economic Education Study Program, at Hamzanwadi University. This research is a quantitative research with a quantitative descriptive approach. The sampling technique used is stratified random sampling and accidental sampling with a total sample of 63 students of the Economic Education Study Program. The data collection technique is using a questionnaire with a 5-point Likert scale. For data analysis techniques using multiple linear regression. The results showed an influence between the marketing mix of purchasing decisions, psychological factors on purchase satisfaction, and situational factors on purchasing decisions except social factors. Therefore, marketing mix, psychological, situational, and social factors influence purchasing decisions.